Deconstructing Patriarchy in Islam: An Analysis of Asma Barlas’ Unreading Concept of the Patriarchal Interpretation of the Quran - Muhammad Tafkir; Zumardin Hidayat; Mohd Anas bin Ayob (Arba: Jurnal Studi Keislaman, 2026)
The dominance of patriarchal interpretation in the treasury of Quranic interpretation has historically shaped hierarchical gender relations and has had direct implications for the legitimacy of social inequality between men and women. Although studies on Islamic feminism and Asma Barlas’s thoughts have developed, most research remains descriptive. It has not yet positioned the concept of unreading as a systematic epistemological critique of the objectivity claims of patriarchal interpretation. This article critically analyzes Asma Barlas’s concept of unreading as a strategy for deconstructing patriarchal interpretations. It evaluates its implications for the renewal of a gender-just methodology in the interpretation of the Quran. This research employs a qualitative method based on literature studies, utilizing a critical hermeneutic approach and epistemological discourse analysis. It involves an in-depth review of Asma Barlas’s primary works and a comparative analysis of classical and modern interpretations of key verses related to gender relations. The results of the study indicate that patriarchy in interpretation is built through three main patterns: first, a literalistic reading that affirms male superiority and removes the ethical context of the Quran; second, the limitation of women’s roles in the public sphere through the naturalization of biological differences into normative hierarchies; and third, the reproduction of masculine religious authority that forecloses the possibility of a plurality of meanings. Barlas’s concept of unreading serves as an epistemological critique that rejects the neutrality of such interpretations by affirming monotheism, justice, and equality as the normative hermeneutic principles of the Quran. In conclusion, the unreading approach not only destabilizes the hegemony of patriarchal interpretations but also provides an alternative methodological framework that significantly contributes to the development of a more egalitarian and inclusive Quranic interpretation in contemporary Islamic studies.